2021
DOI: 10.1029/2021gl095795
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Drainage Reorganization Driven by Rapid Lake Growths on the Tibetan Plateau

Abstract: Drainage reorganization generally occurs on geological time scales under unstable river network conditions. A few local‐scale studies indicate that recent climatic changes might accelerate the drainage reorganization process. However, large‐scale drainage reorganization during the modern era is rarely documented. This study examines ongoing drainage reorganization on the endorheic Tibetan Plateau (TP) as a primary result of drastic lake expansion. A total of 11 drainage system reorganization events comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In the calculation formula, ΔV represents the change of lakewater volume in two periods, A 1 and A 2 represent the area of the lake in different periods, respectively, with lake area A 1 and level H 1 for the previous period and lake area A 2 and level H 2 for the later period. This method has been frequently used in estimating lake water volume (Liu et al, 2021;Lu et al, 2021).…”
Section: Lake Water Volume Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the calculation formula, ΔV represents the change of lakewater volume in two periods, A 1 and A 2 represent the area of the lake in different periods, respectively, with lake area A 1 and level H 1 for the previous period and lake area A 2 and level H 2 for the later period. This method has been frequently used in estimating lake water volume (Liu et al, 2021;Lu et al, 2021).…”
Section: Lake Water Volume Calculationmentioning
confidence: 99%
“…Although these reorganization events occurred in the endorheic basins, the results showed that the significant increase in the Salt Lake water volume could overflow to the adjacent exorheic basin, seriously threatening the engineering construction. In the worst-case scenario, the outburst flood from Salt Lake can destroy engineering infrastructure within 6 hours (Liu et al, 2021). In the end, to reduce the impact of the potential Salt Lake outburst, the local government constructed a drainage channel to divert the lake water into the Qingshui River, which also led to the endorheic-exorheic transition (Lu et al, 2021).…”
Section: Implications Of the Endorheic-exorheic Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lakes with the most remarkable level-rising rates behavior in locally inconsistent patterns, which are found in several medium-sized basins (Salt Water Lake: 35.61 m, Yibug Caka: 20.30 m, and Xuejing Lake: 17.83 m) around the western and middle Kunlun Mountains. Another exception is Salt Lake, which had an abnormal rise of 16.27 m in water level due to the substantial upstream water supply from the Zhuonai Lake outburst (Liu et al 2016, Liu et al 2021b. Of the 160 lakes examined, 121 and 39 are endorheic and exorheic lakes, respectively (table S1 (available online at stacks.iop.org/ERC/4/091002/mmedia)).…”
Section: Lake Salinity Changes With Water Storage Variationsmentioning
confidence: 99%
“…That was because this small and shallow lake experienced more than 16 m level rise and 4.5 times area expansion after the upstream lake outburst in 2011. Its salinity would get much lower as the Chinese government constructed an artificial channel in 2019 and made it become an outflow lake, being linked with the upstream Yangtze (Liu et al 2021b, Lu et al 2021. Other lakes that experienced obviously reduced salinity include Norma Co (43.40 g l −1 to 4.91 g l −1 ), Cedo Caka (168.39 g l −1 to 19.50 g l −1 ), Serbug Co (28.35 g l −1 to 4.31 g l −1 ), Dogaicoring Qangco (266.35 g l −1 to 42.00 g l −1 ), and Angdar Tso (180.87 g l −1 to 32.50 g l −1 ), etc.…”
Section: Lake Salinity Changes With Water Storage Variationsmentioning
confidence: 99%